1998
DOI: 10.1063/1.122424
|View full text |Cite
|
Sign up to set email alerts
|

Probing interfacial and bulk magnetic hysteresis in roughened CoFe thin films

Abstract: The hysteretic behavior of interfacial magnetic moments for CoFe thin films with varying roughness is determined in an element specific manner by monitoring the applied magnetic field dependence of the specular and off-specular (diffuse) contributions to the x-ray resonant magnetic scattering signal. Increasing the interfacial roughness generates a larger variation of the relative coercive field associated with the interfacial moment in comparison to the bulk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…7 Very recently, Freeland et al using the x-ray resonant magnetic scattering studied hysteretic behavior of CoFe thin films with varying roughness. 8 They also found the coercivity increased with the surface roughness. The other kind is a film with double rough boundaries.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…7 Very recently, Freeland et al using the x-ray resonant magnetic scattering studied hysteretic behavior of CoFe thin films with varying roughness. 8 They also found the coercivity increased with the surface roughness. The other kind is a film with double rough boundaries.…”
Section: Introductionmentioning
confidence: 92%
“…Nonetheless, how does the detailed morphology of the surface affects the apparent coercivity was not considered in most experiments. [6][7][8]10 Only a few experiments relate the change in coercivity to the change of the interface width w. Recently, some detailed works have been performed. 5,9 Experiments of Co films: In the following we shall discuss the connection of our theory and our experimental work.…”
Section: Connections With Experimentmentioning
confidence: 99%
“…Vilain et al 3 investigated the coercivity versus surface roughness of NiCo alloy films and Malyutins et al 4 showed that the coercivity of chemically etched Ni-Fe-Co films increases with the surface roughness. Frealnd et al 5 studied hysteretic behavior of CoFe thin films with varying roughness using the X-ray resonant magnetic scattering. It has been found that, the coercivity increased with the surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…The dependence of the diffuse scattering on the applied magnetic field provides information on the domain structure in the film plane and on the spin disorder at the interfaces [27][28][29]. Hase et al have shown that the diffuse scattering around the half-order magnetic peak in AF coupled magnetic superlattices is of pure magnetic origin [30].…”
mentioning
confidence: 98%